Moral courage in nursing – An integrative literature review. (15th February 2021) - Pajakoski, Elina; Rannikko, Sunna; Leino‐Kilpi, Helena; Numminen, Olivia
Abstract: Moral courage and understanding of its meaning are essential when nurses face ethical conflicts in their practice. This integrative review aimed to explore moral courage in nursing and possible associated individual and organizational factors. A database search in January 2020 identified 1308 scientific articles of which 25 were selected for the review. Inductive analysis with clear steps for defining and synthesizing themes in research reviews revealed three categories concerning moral courage in nursing: definition and descriptions of moral courage, characteristics of the morally courageous nurse, and skills and acts of the morally courageous nurse. Individual and organizational factors, such as positive personal experiences, commitment to ethical principles, supportive work environment and teamwork, were associated with moral courage in nursing, contributing to a more comprehensive description of nurses' moral courage. Findings indicate that in nursing practice, there is a need for promoting multi‐professional collaboration and discussion of ethical dilemmas to provide opportunities to enhance moral courage. Developing care environments in which hierarchy does not inhibit nurses' moral courage seems justified. Further research on moral courage with varying methodologies and multi‐disciplinary and international approaches is needed.